High-Throughput Sequencing Approach to Analyze the Effect of Aging Time and Barrel Usage on the Microbial Community Composition of Red Wines - Kioroglou, Dimitrios; Mas, Albert; Portillo, Maria C. (Frontiers in Microbiology, 2020)
Wine aged in barrels or bottles is susceptible to alteration by microorganisms that affect the final product quality. However, our knowledge of the microbiota during ageing and the factors modulating the microbial communities is still quite limited. The present work uses high throughput (HTS) techniques to deal with the meta-taxonomic characterization of microbial consortia present in red wines along 12 months ageing. The wines obtained from two different grape varieties were aged at two different cellars and compared based on time of wine ageing in the barrels, previous usage of the barrels and differences between wine ageing in oak barrels or glass bottles. The ageing in barrels did not affect significantly the microbial diversity but changed the structure and composition of fungal and bacterial populations. The main microorganisms driving these changes were the bacterial genera Acetobacter, Oenococcus, Lactobacillus, Gluconobacter, Lactococcus and Komagataeibacter and the fungal genera Malassezia, Hanseniaspora and Torulaspora. Our results showed that the oak barrels increased effect on the microbial diversity in comparison with the glass bottles, in which the microbial community was very similar to that of the wine introduced in the barrels at the beginning of the ageing. Furthermore, wine in the bottles harbored higher proportion of Lactobacillus but lower of Acetobacter. Finally, it seems that one year of previous usage of the barrels was not enough to induce significant changes in the diversity or composition of microbiota through ageing compared with new barrels. This is the first meta-taxonomic study on microbial communities during wine ageing and shows that the microorganism composition of barrel-aged wines was similar at both cellars. These results hint the possibility of a common and stable microbiota after ageing in the absence of exogenous alterations. Further corroborations on the current outcome would be valuable for the comparison and detection of microbial alterations during ageing that could potentially prevent economic losses in the wine industry.